1993
DOI: 10.1002/eji.1830230417
|View full text |Cite
|
Sign up to set email alerts
|

In vivo induction of the nitric oxide pathway in hepatocytes after injection with irradiated malaria sporozoites, malaria blood parasites or adjuvants

Abstract: The mechanisms responsible for malarial immunity induced by repetitive injections of X-irradiated sporozoites have not been fully established. We demonstrate here that a single injection of irradiated sporozoites induced, as soon as 24 h after, a non-permissive state to hepatocyte reinfection with sporozoites in vitro. The same effect was observed when malarial blood forms, irradiated promastigotes of Leishmania infantum, adjuvants (muramyl dipeptide, poly acidylic uridylic) or interferon-gamma was injected. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 34 publications
6
58
1
1
Order By: Relevance
“…The protection induced by spz/CQ immunization was found to be strictly dependent on NO, as inhibition of inducible NO synthase by treatment with a highly specific inhibitor, S-methyl-thiourea (21) completely reversed protection (Table VI). Previous work has shown that LS parasites are susceptible to radical nitrogen intermediates induced by different cytokines (IFN-␥, IL-6, or TNF-␣) or after immunization with irr.spz (32,(35)(36)(37). Thus, our results imply that in our immunization model, other cytokines may lead to NO-mediated killing.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The protection induced by spz/CQ immunization was found to be strictly dependent on NO, as inhibition of inducible NO synthase by treatment with a highly specific inhibitor, S-methyl-thiourea (21) completely reversed protection (Table VI). Previous work has shown that LS parasites are susceptible to radical nitrogen intermediates induced by different cytokines (IFN-␥, IL-6, or TNF-␣) or after immunization with irr.spz (32,(35)(36)(37). Thus, our results imply that in our immunization model, other cytokines may lead to NO-mediated killing.…”
Section: Discussionsupporting
confidence: 52%
“…The observation of some protection in the absence of IFN-␥R signaling suggests that an alternative pathway is operating (Table V). This pathway, however, does not seem to involve other cytokines such as IL-12, IL-6, or TNF-␣ (Table VI), which have been shown previously to inhibit LS development (32)(33)(34)(35)(36). The protection induced by spz/CQ immunization was found to be strictly dependent on NO, as inhibition of inducible NO synthase by treatment with a highly specific inhibitor, S-methyl-thiourea (21) completely reversed protection (Table VI).…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, iNOS-derived NO regulates wound contraction, collagen formation, and cell proliferation. In addition, NO has strong antimicrobial activity and its importance in antimalarial immunity has been well documented (22,23). To assess the ability of sporozoites to induce iNOS expression in hepatocytes, HepG2 cells were incubated with either sporozoites or salivary gland material of uninfected mosquitoes (sgm) and iNOS expression was assessed at different time points.…”
Section: Nf-b-regulated Inos Expression In Hepatocytes Reduces the Numentioning
confidence: 99%
“…In particular, NO regulates the contraction of wounds, collagen biosynthesis, and cell proliferation, although the precise mechanism is unknown. In addition, several studies have demonstrated that NO is of central importance in anti-malarial liver immunity (21)(22)(23). Due to the many dramatic effects of iNOS activity, its expression has to be tightly controlled.…”
mentioning
confidence: 99%
“…3 The liver and blood stages of P. falciparum are thought to proceed independently of one another. However, it has been suggested that in murine models of malaria infection, high blood-stage parasitemia may inhibit the development of subsequent liver-stage infections [4][5][6] ; this is thought to occur indirectly as a result of stimulation of inflammatory pathways, and possible roles for nitric oxide and hepcidin in inhibiting liver-stage parasite development have been proposed. A possible evolutionary advantage for the parasite is that one parasite strain suppresses the growth of late-arriving competitor strains, 6 and this observation opens the potential for therapeutic intervention to suppress infection.…”
Section: Introductionmentioning
confidence: 99%